Os limites da autoridade parental frente aos direitos fundamentais da criança e do adolescente nas relações familiares - Nilsson, Gunnar (2012)
The present research analyzes the efficiency of fundamental rights of children and teenagers as well as the application of the best interests of the children and teenagers in familiar relationships. This research also will aboard the collision chances between the fundamental rights to freedom, to respect, to dignity and to family and conviviality and the living in communities compared with the duties inherent parental authority, pointing a thinking as criterion to solve the cases of collision of fundamental rights. It seems to be that the fundamentals rights of children and teenagers have a straight efficiency in family relationships as well as the adoption of duty theory of protection should cover in threats and aggressions coming from others, pointing ensure the best interest of the children. In the first part we will treat about the evolution of the institute of parental authority, then for Roman Law school, then to Civil Right, encoded and for Federal Constitution, even by his current configuration. In the second part of research it will analyze the Doctrine of Integral Protection, the principle of best interest of children, the fundamentals rights of juveniles and the theories of efficiency fundamental rights in the relation of privates, as in his Germanic origin, as in the current situation of Brazilian scenery. In the third part we will review first, the evolution of family relations between parents and children of modernity to post-modernity. Later enter in the effectiveness of the fundamental rights of children and adolescents in family relationships, especially the direct effectiveness of fundamental rights for children and juveniles in family relationships, and the theory of obligations in ensuring protection against any threats from rights of third parties.Cover-if you have the chances of a collision between the fundamental rights of children-juveniles and duties inherent in parental authority, pointing out some criteria for resolving them, aiming always the guarantee of the best interests of children and adolescents.